Road Traffic Injuries: A Challenge for Iran's Health System - A Ardalan; GR Masoomi; MM Goya; MR Sarvar; M Haddadi; J Miadfar; F Rezvani; M Shahmoradi (Tehran University of Medical Sciences, 2009)
Road traffic injury (RTI) was the leading cause of premature death and disability in I.R.Iran, measured by disability-adjusted life-year (DALY) in 2003. In this paper, we describe the progress and challenges of health system dealing with RTI. MOH&ME has initiated or contributed in national efforts with collaboration of Police, Ministry of Road & Transportation (MoRT), media and Iranian Red Crescent Society (IRCS). As for the pre-crash and crash phases, EMC works on Safe Community (SC) project and public awareness. To minimize the risk of post-crash phase, MOH&ME has enhanced the EMS capacity in terms of technical, equipmental and operational, which has led to coverage of 95% of mass casualty incidents and decreasing the "to scene" and "transport" times. Despite the 16.9% decreasing number of RT-related death in 2007, Iran is in the highest rank in the world. RTI prevention needs a national concerted campaign with collaboration of health system and all other concerned partners. The most costly interventions are those deals with road design and safety during pre-crash and crash phases. But, focusing on people through awareness of safe traffic behavior with combination of low enforcement, would lead decreasing the RTI in shorter time. Health system needs to focus on groups at the highest risk, including urban accidents and young men drivers. Increasing the quality and coverage of EMS, road risk assessment and close intersectoral collaboration would assist health system on the prevention programs. Injury research and surveillance are the basis for effective injury prevention.